2013
DOI: 10.1111/tct.12029
|View full text |Cite
|
Sign up to set email alerts
|

When should students learn about ethics, professionalism and patient safety?

Abstract: The Intensive was designed to demonstrate to students the importance of PPD. A counter position is that students lack the clinical context required for effective learning of PPD topic areas. We discuss these conflicting beliefs and the changes made to the Intensive programme in 2010. As a result of the lessons, we changed the 2010 Intensive programme to strongly emphasise professionalism; patient safety was moved to the later years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…The other aims to train citizens in order to make them aware of the common good and their commitment as professionals 7 . The theoretical knowledge of ethics is put into practice in the daily life of the physician, materialising in real cases that are judged according to principles and values internalised in the person 3,11,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other aims to train citizens in order to make them aware of the common good and their commitment as professionals 7 . The theoretical knowledge of ethics is put into practice in the daily life of the physician, materialising in real cases that are judged according to principles and values internalised in the person 3,11,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to seize concepts of medical ethics in training, given their extreme need in the preparation of physicians 5,21,[35][36][37][38] when establishing ethical conduct in the scientific, technological, biological and health fields 2,7 . However, this research revealed low overall performance of G1, which, when added to the cases of superior performance of G2, shows that the instruction of students, even among those who attended at least one of the two disciplines that address medical ethics, is insufficient to deal with other dilemmas.…”
Section: Dilemmas Section In Clinical Casesmentioning
confidence: 99%
“…La question de savoir à quel moment dispenser un enseignement se pose régulièrement. C'est en particulier le cas pour les notions d'éthique, de relation et de positionnement avec les patients 28 . Certains enseignants profitent des cours de sciences fondamentales pour éduquer aux grandes notions déontologiques, comme le secret professionnel, avant que les élèves n'aillent en stage 29 .…”
Section: Discussionunclassified
“…Junior clinicians often experience difficulties applying their patient safety knowledge in the hierarchical healthcare workplace 58. More experienced health professionals who have developed an understanding of the wider systems issues associated with unsafe care can more easily apply their learning in the clinical environment 59. Learning patient safety in the clinical environment is therefore more appropriate for teaching advanced trainees how to use the patient safety skills and knowledge taught in medical school.…”
Section: Discussionmentioning
confidence: 99%